The Palgrave handbook of age diversity and work - Parry, Emma; McCarthy, Jean (Palgrave Macmillan, 2017)
This Handbook incorporates a variety of disciplines and approaches in order to provide a comprehensive and authoritative examination of the issues that result from increasing age diversity at work. Despite interest in this area exploding over the past few years amongst academics, practitioners and policy makers, the analysis of age diversity has remained primarily within disciplinary 'silos' such as Psychology or Sociology with a focus on ageing or generational differences, rather than a combination of approaches to understanding age diversity. Unique in its coverage of multiple perspectives, it considers not only generational and ageing perspectives to age diversity, but also highlights the importance of context in driving both the impact and response to this issue. The Palgrave Handbook of Age Diversity and Work includes contributions from leading scholars in age and generational diversity from across the world, discussing cutting-edge research findings about the nature and impact of age diversity and presenting approaches to managing this phenomenon.- Resumé vydavatel
Keywords: senioři; generační rozdíly; práce; generace Y; personální management; older people; generational differences; labor; generation Y; personnel management; elektronické knihy; sborníky; electronic books; papers of several authors